Indices of social development and their application to Africa - Arjan de Haan; Roberto Foa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper, using a new set of social development indices, explores the measurement of social development across Africa, and how this relates to broader development patterns and measurement. Development practitioners worldwide increasingly recognize the importance of informal institutions, such as trust, associations and inclusion, and their impact on well-being, poverty, growth or aid effectiveness. However, there has been little empirical analysis that tests these relationships, largely because of data limitations. The Indices of Social Development, hosted by the International Institute of Social Studies is a large and innovative database of social development indicators to overcome such data constraints. They are based on over 200 measures from 25 data sources for the years 1990 to 2010, aggregated into six composite indices: civic activism, inter-personal safety and trust, inter-group cohesion, clubs and associations, gender equality, and inclusion of minorities. This paper presents how the database can be used to compare the Africa region to global patterns, analyse divergence across the continent, and explore the implications for our understanding of inclusive growth in Africa.
Keywords: E01; I32; 330; measurement; social development; well-being; indicators